Prolonged “Chair” Sitting - Detrimental to Workplace Health - Philip W Scruggs (Academic Chairpersons Conference Proceedings, 2016)
Session participants and the presenter will share, discuss and challenge experiences and insights of successes and challenges with policy (e.g., faculty and staff activity participation), environmental (e.g., sit-stand desks, walking meetings, active deliveries, etc.) and cultural (e.g., physical activity as a legitimate workplace behavior) changes for a healthy active workplace.
Keywords: Health-enhancing; Physical activity; Productive; Workplace environment; Sitting time